2021
DOI: 10.1152/ajpcell.00432.2020
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the E3 ubiquitin ligase UBR5 and its role in skeletal muscle anabolism

Abstract: UBR5 is an E3-ubiquitin-ligase positively associated with anabolism, hypertrophy and recovery from atrophy in skeletal muscle. The precise mechanisms underpinning UBR5's role in the regulation of skeletal muscle mass remains unknown. The present study aimed to elucidate these mechanisms by silencing the UBR5 gene in-vivo. To achieve this aim, we electroporated a UBR5-RNAi plasmid into mouse tibialis anterior muscle to investigate the impact of reduced UBR5 on mechano-transduction signalling MEK/ERK/p90RSK and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…As these genes all demonstrated reduced hypomethylated signatures after acute RE in humans, data reported herein demonstrate only a minor congruence with the changes observed after acute RE in humans (Turner et al, 2019b ). Finally, given UBR5 hypomethylation and increased gene expression has been extensively characterized under various anabolic conditions across species (Hughes et al, 2020 ; Seaborne et al, 2018b , 2018a , 2019 ) together with demonstrating the largest increases in gene expression compared with any other gene analyzed in the present study, we analyzed its DNA methylation at both 0.5 h (described above) and 3 h post‐loading. Despite robust increases in gene expression at both 0.5 h (1.77‐fold) and 3 h (2.34‐fold) postloading, there was no change in DNA methylation observed at 0.5 h (described above in Figure 5b ) and 3 h post‐loading in the bioengineered muscle (Figure 7f ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As these genes all demonstrated reduced hypomethylated signatures after acute RE in humans, data reported herein demonstrate only a minor congruence with the changes observed after acute RE in humans (Turner et al, 2019b ). Finally, given UBR5 hypomethylation and increased gene expression has been extensively characterized under various anabolic conditions across species (Hughes et al, 2020 ; Seaborne et al, 2018b , 2018a , 2019 ) together with demonstrating the largest increases in gene expression compared with any other gene analyzed in the present study, we analyzed its DNA methylation at both 0.5 h (described above) and 3 h post‐loading. Despite robust increases in gene expression at both 0.5 h (1.77‐fold) and 3 h (2.34‐fold) postloading, there was no change in DNA methylation observed at 0.5 h (described above in Figure 5b ) and 3 h post‐loading in the bioengineered muscle (Figure 7f ).…”
Section: Resultsmentioning
confidence: 99%
“…In rodent muscle, recent work has also confirmed that UBR5 gene expression and protein levels increase in response to hypertrophy in vivo, with no changes observed in the well‐characterized atrogene E3 ligases, MuRF1 and MAFbx (Seaborne et al, 2019 ). Moreover, its role in muscle mass regulation has been recently determined whereby RNAi induced silencing in Drosophila results in smaller sized larvae (Hunt et al, 2019 ) and RNAi electroporated into mouse TA muscle in vivo leads to atrophy via reduced protein synthesis and dysfunctional ERK/Akt signaling (Hughes et al, 2020 ). Collectively, such data support the notion that UBR5 is important for load‐induced anabolism and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Further, even greater hypomethylation was observed if exercise training had been undertaken previously, such as following retraining (Seaborne et al, 2018a,b). For example, the candidate gene ubiquitin protein ligase E3 component N-recognin 5 (UBR5) demonstrating this epigenetic profile, has now been determined as an important regulator of skeletal muscle mass (Seaborne et al, 2019;Hughes et al, 2021). Therefore, alterations in DNA methylation signatures are emerging as important drivers in the molecular response to exercise and subsequent physiological adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Rad6 (E2) is known to function with Poe (E3) in its N-end rule regulation of proteins involved in vesicular trafficking and the lysosomal pathway (Hong, 2015). Hyd (E3) has been studied in context of the N-end rule in regulating Hedgehog signaling, oogenesis, and immune response in Drosophila (Cammarata-Mouchtouris, 2020;Dorogova, 2020;Moncrieff, 2015), while its human ortholog UBR5 was studied in ovarian cancer signaling, tissue homeostasis, and miRNA mediated translational control (Cho, 2017;Hughes, 2021;Mellis, 2021;Tasaki, 2012). Finally, while UbcD1 (E2) has not been linked to the N-end rule, it does show high similarity to UBC4 (Treier, 1992), which is an E2 known to function with 13 Hyd (E3) /UBR5 in yeast (Stoll, 2011).…”
Section: Discussionmentioning
confidence: 99%